Relationship between pituitary stalk (PS) visibility and the severity of hormone deficiencies: PS interruption syndrome revisited. (7th May 2015) - Wang, Weiqing; Wang, Shuwei; Jiang, Yiran; Yan, Fuhua; Su, Tingwei; Zhou, Weiwei; Jiang, Lei; Zhang, Yifei; Ning, Guang
Summary Context Pituitary stalk interruption syndrome (PSIS) is a rare cause of combined pituitary hormone deficiency characterized by a triad shown in pituitary imaging, yet it has never been evaluated due to the visibility of pituitary stalk (PS) in imaging findings. Objective The major objective of the study was to systematically describe the disease including clinical presentations, imaging findings and to estimate the severity of anterior pituitary hormone deficiency based on the visibility of the PS. Methods This was a retrospective study including 74 adult patients with PSIS in Shanghai Clinical Center for Endocrine and Metabolic Diseases between January 2010 and June 2014. Sixty had invisible PS according to the findings on MRI, while the rest had a thin or intersected PS. Basic characteristics and hormonal status were compared. Results Of the 74 patients with PSIS, age at diagnosis was 25 (22–28) years. Absent pubertal development (97·3%) was the most common presenting symptom, followed by short stature. Insulin tolerance test (ITT) and gonadotrophin‐releasing hormone (GnRH) stimulation test were used to evaluate the function of anterior pituitary. The prevalence of isolated deficiency in growth hormone (GH), gonadotrophins, corticotrophin and thyrotrophin were 100%, 97·2%, 88·2% and 70·3%, respectively. Although the ratio of each deficiency did not vary between patients with invisible PS and with visible PS, panhypopituitarism occurred significantly more frequent in patients with invisible PS. Patients with invisible PS had significantly lower levels of luteinizing hormone (LH), follicle stimulation hormone (FSH) and hormones from targeted glands including morning cortisol, 24‐h urine free cortisol, free triiodothyronine (FT3), free thyroxine (FT4) and testosterone (T) in male than patients with visible PS. Moreover, patients with invisible PS had lower peak LH and FSH in GnRH stimulation test, and higher peak cortisol in ITT while peak GH remained unchanged between two groups. Conclusions The prevalence of multiple anterior pituitary hormone deficiency was high in adult patients with PSIS. And more importantly, we found the visibility of PS shown on MRI might be an indication of the severity of PSIS.